Pengaruh Kualitas Audit Dan Pertumbuhan Perusahaan Terhadap Pemberian Opini Audit Wajar Dengan Pernyataan Going Concern Pada Perusahaan Manufaktur Di Bursa Efek Indonesia: Pengaruh Kualitas Audit Dan Pertumbuhan Perusahaan Terhadap Pemberian Opini Audit Wajar Dengan Pernyataan Going Concern Pada Perusahaan Manufaktur Di Bursa Efek Indonesia - Yusrita, Yusrita (UNIVERSITAS SARI MUTIARA INDONESIA, 2017)
One way to provide high quality information is to audit the financial statements done by an internal audit of the company or by a public accountant. But for companies that have gone public have an obligation to conduct an audit of financial statements by an external auditor (public accountant). Expected later to do his confidence the audit - the users of the company will also increase. The greater the reputation of the firm that audited, the higher the confidence of users of financial statements. The purpose of this study was to determine whether the Audit Quality and the Net Profit Margin affect the going concern opinion on Manufacturing Company in Indonesia Stock Exchange in the year 2012 – 201 4 either partially or simultaneously. The population in this research is manufacturing companies listed in Indonesia Stock Exchange as many as 136 companies. The sampling method in this research using purposive sampling method by 95 companies. Data collection methods used in this study will use logistic regression method. The results of this study indicate that audit quality is not significantly influence the going concern opinion on companies listed in the Indonesia Stock Exchange, while the net profit margin significantly influence the going concern opinion on manufacturing companies listed in Indonesia Stock Exchange. Quality Audit Capabilities and the Net Profit Margin in explaining the going concern opinion amounted to 73.6% while the remaining 26.4% explained by other variables not included in this research model. Keywords: Quality Audit, Net Profit Margin, going concern opinion